2021
DOI: 10.1039/d1sc02265b
|View full text |Cite
|
Sign up to set email alerts
|

The exchange of the fast substrate water in the S2 state of photosystem II is limited by diffusion of bulk water through channels – implications for the water oxidation mechanism

Abstract: The molecular oxygen we breathe is produced from water-derived oxygen species bound to the Mn4CaO5 cluster in photosystem II (PSII). Present research points to the central oxo-bridge O5 as the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 103 publications
2
35
0
Order By: Relevance
“… 32 34 , 50 , 57 In addition to methodological differences, these studies modeled a Ca 2+ -bound W3 in the S 3 Y z state, 25 , 26 and an additional water molecule (W x ) bound to Mn1/Mn4. Recent experiments have further supported W3 as a substrate water molecule, 37 39 whereas previous experimental assignment supported W2. 27 30 We also note that rotation of the Mn4 ligands, as observed in the present ( Figure S3D ) as well as previous QM/MM simulations, 51 could exchange the identity of the water molecules.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“… 32 34 , 50 , 57 In addition to methodological differences, these studies modeled a Ca 2+ -bound W3 in the S 3 Y z state, 25 , 26 and an additional water molecule (W x ) bound to Mn1/Mn4. Recent experiments have further supported W3 as a substrate water molecule, 37 39 whereas previous experimental assignment supported W2. 27 30 We also note that rotation of the Mn4 ligands, as observed in the present ( Figure S3D ) as well as previous QM/MM simulations, 51 could exchange the identity of the water molecules.…”
Section: Discussionmentioning
confidence: 95%
“…Ugur et al ( 26 ) suggested that W3-deprotonation triggers the migration of this water molecule toward Mn1 (or to Mn4 in the closed cubane form), in a process that is favored by the oxidation of Tyr z , a finding that has recently gained indirect support from time-resolved X-ray free electron laser (XFEL) structures of PSII in the S 2 Y z → S 3 Y z transition 23 (but cf . also refs ( 35 ) and ( 36 )), Fourier transform infrared (FTIR) spectroscopic studies, 37 , 38 time-resolved membrane inlet mass spectrometric (TR-MIMS) experiments, 39 and other computational studies. 40 Importantly, water-exchange experiments revealed that all substrate water molecules are already bound in the S 2 Y z state 27 and that the (water/hydroxo/oxo) ligands observed in the refined X-ray structural models of this state 7 , 9 , 11 , 23 are thus likely substrate water candidates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the S 2 -to-S 3 and S 3 -to-S 4 transitions, proton deprotonation precedes the oxidation of the Mn 4 Ca cluster. The cluster is surrounded by an extensive network of H-bonds that merge into three well-defined pathways that lead to the thylakoid lumen. These pathways facilitate proton egress and/or substrate water access. , , …”
Section: Introductionmentioning
confidence: 99%
“…In photosystem II, the Mn 4 CaO 5 cluster is situated within a large protein complex in which the access of water is regulated by three channels. In addition, the water molecules near the Mn 4 CaO 5 cluster are arranged mainly along one face of the cluster, and they are highly ordered due to H-bonding networks that are supported by specific amino acids. In case of molecular WOCs, the bulk water access may be limited by water/inert solvent mixtures (e.g., 3 M water in MeCN) or, more specifically, by embedding the catalyst in matrices such as MOFs, redox active polymers, or designed polypeptides/proteins …”
Section: Discussionmentioning
confidence: 99%